Novel Spanish translators for acute care nurses and physicians: usefulness and effect on practitioners' stress. - Bernard AC; Summers A; Thomas J; Ray M; Rockich A; Barnes S; Boulanger B; Kearney P (American Journal of Critical Care, 2005)
BACKGROUND Language barriers are significant impediments to providing quality healthcare, and increased stress levels among nurses and physicians are associated with these barriers. However, little evidence supports the usefulness of a translation tool specific to healthcare. OBJECTIVES To evaluate the effectiveness of a novel English-Spanish translator designed specifically for nurses and physicians. The hypothesis was that the translator would be useful and that use of the translator would decrease stress levels among nurses and physicians caring for Spanish-speaking patients. METHODS Novel English-Spanish translators were developed entirely on the basis of input from critical care nurses and physicians. After 7 months of use, users completed surveys. Usefulness of the translator and stress levels among users were reported. RESULTS A total of 60% of nurses (n = 32) and 71% (n = 25) of physicians responded to the survey. A total of 96% of physicians and 97% of nurses considered the language barrier an impediment to delivering quality care. Nurses reported significantly more stress reduction than did physicians (P =.01). Most nurses and physicians had used the translator during the survey period. Overall, 91% of nurses and 72% of physicians found that the translator met their needs at the bedside some, most, or all of the time. All nurses thought that they most likely would use the translator in the future. CONCLUSIONS The translator was useful for most critical care nurses and physicians surveyed. Healthcare providers, especially nurses, experienced decreased stress levels when they used the translator.